On the uniqueness of a solution of the inverse problem for a simple-layer potential - Kapanadze, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We prove the uniqueness of solution of the inverse problem of single-layer potential for star-shaped smooth surfaces in the case of the metaharmonic equation Δv - K² v = 0. For the Laplace equation, a similar statement is not true.